How to succeed with continuous improvement : a primer for becoming the best in the world - Ahlstrom, Joakim (McGraw-Hill Education, 2015)
Joakim Ahlstrom, one of the world's most respected continuous improvement experts, takes readers through a real-life case study of one organization's journey to a world-class continuous improvement process. In each chapter, he describes a specific stage of the transformation story and provides a clear analysis of each one to help readers apply his methods in their own companies. Topics include: how to shift mindsets and behaviors using the often neglected practice of coaching; common pitfalls to help plan out how to apply the principles and practices; using "six-legged spiders" and "fishy" diagrams to achieve measurable results; ways to avoid "Watermelon" key performance indicators that often mask the truth. Ahlstrom explains rationale behind all the methods in the book, the results they produce and why, and offers practical advice on how to get full input from everyone involved. --